(untitled) (Experimental biology, 2022)
Coronaviruses are a large family of RNA-containing viruses capable of infecting humans and a number of animal species. Several species of coronaviruses are now known to circulate in the population and generally cause moderate to severe upper respiratory tract and lung disease. A new coronavirus infection, COVID-19 (SARS-CoV-2), has been added to this list. The virus has spread rapidly around the world. Recently in Kazakhstan, this infection has been observed with pronounced pneumonia among the population. In developing the vaccine, we had to work with live SARS-CoV-2 virus. It should be noted that when working with live virus, we faced some issues concerning the biological and physicochemical properties of the virus, which have remained outside the attention of scientists of the world. In this connection, in these studies we studied some physicochemical and biological properties of Kazakh strain of SARS-CoV-2 virus isolated from a patient with new coronavirus infection COVID-19, such as thermal stability (persistence), virus inactivation by different concentrations of formaldehyde at different temperature and time regimes and virus passivation in cell culture. Studies were conducted to find additional biological models sensitive to the SARS-CoV-2 virus and used in vitro. Of the 11 cell culture species tested, monkey and pig cell cultures were found to be the most sensitive to the SARS-CoV-2 virus, in which the virus was actively reproducing. We studied the effect of storage conditions of SARS-CoV-2 nucleic acid samples as well as the effect of environmental conditions on the SARS-CoV-2 virus itself. The results of our studies showed that freezing at minus 70 оС and thawing at room temperature (20-22 оС) had no appreciable effect on the qualitative character of cytopathogenicity but had a negative effect on the preservation of virus titer. Data on the effects of chemical factors when working with pathogens are necessary to create conditions of biological safety for personnel and the environment, as well as the design of technologies for the manufacture of biological products for diagnostic and prophylactic purposes. In this study, we studied the effect of formaldehyde to the virus. The results obtained show that inactivation of Sars-CoV-2 virus with formalin depends on formaldehyde concentration, reaction temperature, incubation time.